Margree, Victoria (2019): British Women’s Short Supernatural Fiction, 1860-1930. Our Own Ghostliness, Palgrave Macmillan. ISBN 978-3-030-27141-1 - Raquel de la Varga Llamazares (Universitat Autònoma de Barcelona, 2021)
Margree, Victoria (2019): British Women’s Short Supernatural Fiction, 1860-1930. Our Own Ghostliness, Palgrave Macmillan. ISBN 978-3-030-27141-1